Neutrophil elastase as a biomarker for bacterial infection in COPD - Thulborn, Samantha J. (Respir Res, 2019)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is predominantly associated with neutrophilic inflammation. Active neutrophil elastase (NE) is a serine proteinase, secreted by neutrophils, in response to inflammation and pathogen invasion. We sought to investigate if NE could be used as a biomarker for bacterial infection in patients with COPD. METHODS: NE was quantified using ProteaseTag® Active NE Immunoassay (ProAxsis, Belfast) from the sputum of COPD subjects at stable state, exacerbation and 2 weeks post treatment visit. RESULTS: NE was measured in 90 samples from 30 COPD subjects (18 males) with a mean (range) age of 65 (45–81) years and mean (SD) FEV(1) of 47% (18). The geometric mean (95%CI) of NE at stable state was 2454 ng/mL (1460 to 4125 ng/mL). There was a significant increase in NE levels at an exacerbation (p = 0.003), and NE levels were higher in a bacterial-associated exacerbation (NE log difference 3.873, 95% CI of log difference 1.396 to 10.740, p = 0.011). NE was an accurate predictor of a bacteria-associated exacerbation (area (95%CI) under the receiver operator characteristic curve 0.812 (0.657 to 0.968). CONCLUSION: NE is elevated during exacerbations of COPD. NE may be a viable biomarker for distinguishing a bacterial exacerbation in patients with COPD. TRIAL REGISTRATION: Leicestershire, Northamptonshire and Rutland ethics committee (reference number: 07/H0406/157).